2023
DOI: 10.3390/nu15061505
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Body Mass Index and Probable Sarcopenia in Community-Dwelling Older Adults

Abstract: (1) Background/Objectives: The relationship between body mass index (BMI) and probable sarcopenia, a precursor to sarcopenia diagnosis, is unclear. While low BMI has been associated with sarcopenia risk, some evidence suggests that obesity may confer protection. We aimed to investigate the association between probable sarcopenia and BMI and, furthermore, to explore associations with waist circumference (WC). (2) Methods: This cross-sectional study included 5783 community-dwelling adults (mean age 70.4 ± 7.5 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…Higher hip circumference being a surrogate measure of gluteal musculature is understandably inversely associated with sarcopenia [ 19 , 74 76 ]. In addition, our study finds that a higher BMI is also protective of sarcopenia similar to other studies [ 18 , 77 79 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Higher hip circumference being a surrogate measure of gluteal musculature is understandably inversely associated with sarcopenia [ 19 , 74 76 ]. In addition, our study finds that a higher BMI is also protective of sarcopenia similar to other studies [ 18 , 77 79 ].…”
Section: Discussionsupporting
confidence: 91%
“…illustrates the characteristics of our participants with corresponding unadjusted odds ratios of sarcopenia. The median age of participants was 75 years old [IQR:[70][71][72][73][74][75][76][77][78][79][80][81], with more females [60.3%] than male participants, and majority [93%] were Chinese. Slightly more than half [56.1%] were currently married.…”
mentioning
confidence: 99%
“…Our study highlighted the significant impact of being underweight on the failure of NGT removal. A BMI below 20 is widely acknowledged as an indicator of malnutrition, and a low BMI is correlated with a higher probability of probable sarcopenia [24,25]. Previous studies have also indicated a link between malnutrition and dysphagia [26], and there is evidence of a relationship between sarcopenia and decreased swallowing function, particularly among older adults in Japan [27].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, sarcopenia was associated with an increased risk of postoperative complications in patients undergoing gastrointestinal surgery (22). However, caution is needed, as the relationship between sarcopenia and BMI is complex (23).…”
Section: Discussionmentioning
confidence: 99%